Promoting Organizational Performance Through Strategic Management of Selected Commercial Banks in Delta State - Akpenyi Florence Dumbiri; Odita O. Anthony; Kifordu Anyibuofu Anthony (CV. Proaksara Global Transeduka, 2025)
This study examines how strategic management enhances organizational performance in selected commercial banks in Delta State, Nigeria. The key objectives are to assess the impact of strategic planning, resource allocation, and performance evaluation on bank effectiveness. Using a mixed-methods approach, data were collected from 200 bank employees via surveys and 10 senior managers through in-depth interviews. Analysis was conducted using descriptive statistics and thematic analysis. Findings reveal that strategic planning aligns business goals with market opportunities, resource allocation improves efficiency and profitability, and performance evaluation enhances decision-making and operations. Banks that adopt strategic management practices demonstrate higher customer satisfaction, increased market share, and greater profitability. The study recommends that banks prioritize strategic planning, optimize resource allocation, and implement robust performance evaluation systems. Additionally, fostering a culture of continuous strategic improvement and aligning strategies with market trends is essential. This research contributes empirical insights into strategic management’s role in banking performance, offering valuable guidance for industry leaders.